1639. Lung Transplant Outcomes in Patients with Chronic Respiratory Disease and Pre-Operative Nontuberculous Mycobacterial Disease. (31st December 2020) - McGuffin, Sarah; Lease, Erika D; Bartlett, Lauren E; Goss, Chris; Johnson, Luke M; Jamali, Haya
Abstract: Background: Pulmonary infection secondary to nontuberculous mycobacteria (NTM) is associated with significant morbidity and mortality, especially in individuals with underlying structural lung disease. Such infections are challenging to treat due to high virulence, antibiotic resistance, and the lack of effective and tolerable therapies. At many transplant centers, the isolation of NTM may be considered a contraindication for lung transplantation. Methods: Institutional and referral medical records, microbiology, radiology and pathology databases were reviewed for patients who underwent lung transplantation at the University of Washington between 2006-2020. 8 patients with NTM disease were identified according to the American Thoracic Society (ATS) guidelines. 9 patients with sputum cultures positive for NTM, but not diagnosed with NTM disease were also evaluated. Results: Patients with NTM disease continued antimycobacterial therapy pre- and post-operatively. NTM organisms isolated included M avium complex, M fortuitum, M abscessus, M kansasii, and M fortiutum. In the cohort with NTM-disease, one patient died within a year of transplantation (14%), three died within 1-5 years (43%), and four (51%) are still alive 1-9 years post-transplantation. Only one patient clearly died as a direct cause of the NTM infection, and this occurred early post-transplantation due to disseminated M abscessus infection. Of the other deceased patients with pre-existing NTM disease, one died due to graft rejection at 3 years, one died due to graft rejection with concomitant non-NTM pneumonia at 2 years, and one died due to cardiac arrest at 4 years. In the cohort without NTM disease, none died within 1 year of transplantation, 22% died within 1-5 years, 11% died more than 5 years post-transplant, and 66% are still alive 1-14 years post-transplant. The probability of survival more than 1 year and more than 5 years post-transplant and 38% in patients with NTM-disease, and 100% and 56% in patients without NTM disease. Conclusion: NTM infection in the lung transplant candidate is uncommon and challenging, however successful treatment can occur, perhaps in the setting of certain subspecies and with prolonged combination antimicrobial therapy. Disclosures: All Authors : No reported disclosures